McCance and Widdowson's : the composition of foods - Roe, Mark A.; Finglas, Paul M.; McCance, R. A. (Robert Alexander), 1898-1993; Widdowson, Elsie M. (Elsie May), 1906-; Food Standards Agency (Great Britain); Institute of Food Research (Cambridge : Royal Society of Chemistry, 2002)
43